THE EFFECT OF GREEN COCONUT WATER CONSUMPTION ON THE LEVELS OF DYSMENORRHES IN ADOLESCENTS IN MADRASAH ALIYAH MANARATUL ISLAM SOUTH JAKARTA - YENNY AULYA; CHOLISAH SURALAGA; PUTI NUR ANNISA M; FEBRY MURIARIMI D (CV KULTURA DIGITAL MEDIA, 2022)
Dysmenorrhea is pain during menstruation, usually marked by a feeling of cramps and centered in the abdomen, complaints of menstrual pain can vary from mild to severe. Green coconut water contains calcium and magnesium which can reduce muscle tension and Vitamin C which are natural anti-inflammatory substances that help relieve pain due to menstrual cramps by inhibiting the cyclooxygenase enzyme . This study aims to determine the effect of consuming green coconut water on the level of dysmenorrhea pain in adolescents at Madrasah Aliyah Manaratul Islam, South Jakarta in 2022. This study used a quasi-experimental design with one group pretest and posttest design . Sampling technique using purposive sampling with 30 respondents who experienced dysmenorrhea during menstruation . The instrument used is the NRS (Numerical Rating Scale) assessing pain using a scale of 1-10. Bivariate analysis using the Wilcoxon test . Based on the results of non-parametric statistical analysis, namely by using the Wilcoxon test, the P-value is 0.000 < 0.05 , which means that there is an effect of consumption of green coconut water on the level of dysmenorrhea pain in adolescents at Madrasah Aliyah Manaratul Islam, South Jakarta in 2022. There is a difference between the level of dysmenorrhea pain before and after consumption of green coconut water, so it can be concluded that there is also an effect of consumption of green coconut water on dysmenorrhea pain in adolescents at Madrasah Aliyah Manaratul Islam South Jakarta in 2022.